Production of D-Glyceric Acid by a Two-step Culture Strategy Based on Whole-cell Biocatalysis of Acetobacter tropicalis - B. Wang; Y. Pu; H. G. Gerken; Y. Xie; L. Lin; H. Chen; Y. Lu (Chemical and Biochemical Engineering Quarterly, 2018)
D-Glyceric acid (D-GA) is a promising chemical for minimizing the toxic effect of acetaldehyde. It has been successfully produced by bioprocesses using glycerol as a substrate. However, high concentrations of glycerol are not beneficial for cell growth. A two-step culture strategy was employed to deal with the ambivalent culture conditions between the growth of Acetobacter tropicalis and the biosynthesis of D-GA. The first stage focuses on biomass accumulation with low initial glycerol concentration; the second stage provides D-GA accumulation through whole-cell biocatalysis. Approximately 2-fold of D-GA yield and 4.5-fold of D-GA productivity were gained by the two-step culture strategy compared to the traditional fermentation with 150 g L–1 of glycerol. Our results also showed that A. tropicalis was able to catalyze the conversion of glycerol to D-GA in the presence of up to 10 % methanol. These findings have important implications to enhance D-GA yield by strategy optimization and reduce its cost.